PEMANFAATAN GOOGLE CLASSROOM SEBAGAI MULTIMEDIA PEMBELAJARAN BAGI GURU MADRASAH PADA DIKLAT DI WILAYAH KERJA KEMENAG KABUPATEN CIANJUR - Durahman Durahman (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
Google classroom is a learning application issued by google in learning. The convenience to access via computers and mobile phones is very beneficial for teachers and students in Madrasahs. The goal achieved in this scientific idea is to describe the use of google classroom as an alternative in learning, and making tasks through google classroom. Use of google classroom can provide access to students in learning online and conventional (blanded learning). There is 59,6% response of the training participants is very fun using google classroom and 56,6% response strongly agree goolge classroom can help task of training participant.Key words: google classroom, madrasah, blanded learning